STRUCTURAL PARTICULARITIES OF THE SILVER AND COPPER DOPED SiO₂–CaO–P₂O₅ BASED BIOACTIVE GLASSES - POPESCU, R. A.; MAGYARI, K.; STEFAN, R.; PAPUC, I.; BAIA, L. (Studia Universitatis Babeș-Bolyai Physica, 2015)
Silver and copper oxidesdoped SiO2–CaO–P2O5 based bioactive glasses were obtained and structurally investigated taking into consideration their possible use as biomaterials for bone regeneration. The samples synthesized by the sol-gel method have shown the existence of a preponderantly amorphous structure, as indicated by the X-ray diffraction (XRD) data. The samples were further heat treated at 600 °C and investigated by means of XRD, Fourier Transform Infrared Spectroscopy (FT-IR) and UV-vis spectroscopy. The XRD data revealed features that can be associated with theexistence of apatite like crystallization centers. UV-vis absorption spectra indicate the presence of a small amount of metallic silver in the glass matrix, while the FT-IR spectra of silver and copper doped SiO2–CaO–P2O5 samples shown common characteristics to the bioactive glasses.